KKNM-Bimbingan Belajar dari Rumah (BDR) secara Offline Selama Masa Pandemi Covid-19 bagi Siswa SDN Reba Rana Manggarai Timur NTT - Nasar, Adrianus; Ewar, Herliana Aryanti; Jeluna, Valeria; Nerli, Yasinta; Tancenca, Avelina (Jurnal Pengabdian UNDIKMA, 2022)
This KKNM service activity aims to provide study guidance from home (BDR) and help students understand the subject matter during the Covid-19 pandemic. BDR is carried out offline because students do not have supporting facilities such as smartphones, besides that the internet network at KKN locations is not optimal. The KKNM was held in Compang Congkar Village, East Manggarai Regency, NTT. BDR was conducted for students from class I to class VI SDN Reba Rana with the material following the school’s book guide. Tutoring for learning from home is carried out for three days a week, namely Wednesday, Thursday and Friday. The method used is lecture, discussion and question and answer. The media used during tutoring are printed books and stationery. The result of the activity is that 70% of students understand the material provided and are enthusiastic about participating in the lesson. Tutoring activities during the pandemic are very much needed by students of SDN Reba Rana so that their understanding of the material will increase.